If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16x-4=4(4x-1)
We move all terms to the left:
16x-4-(4(4x-1))=0
We calculate terms in parentheses: -(4(4x-1)), so:We get rid of parentheses
4(4x-1)
We multiply parentheses
16x-4
Back to the equation:
-(16x-4)
16x-16x+4-4=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| -4+-1t+3t^2=0 | | 3(2–x)=5(2x-7)+2 | | 10v–6=8v | | -4+-1t+3t2=0 | | 8v−6v=20 | | 3(x+1)=-2(x-1)/6 | | 3(2x-4)=24x= | | (2x-4)=34 | | 8v6v=20 | | -40+8x=7(7x+6) | | 2|4x-1|=3|4x+2| | | 3x+7=10-22 | | 9a-5a+5=2a-3 | | E^(4x)=26 | | -55n-5=-4n | | -5r+8r+3=0 | | -63=-27x | | 0.5x=0.3x+3.5 | | -4h^2-16h=0 | | 8/5-4x=0.7 | | 2.7p-4=1 | | 10x-9=8x+(-4) | | 54=2(3w-4)+2w | | X=11y-140 | | -4(2x+2)=(-4(x+1))/4 | | 3n+7+3n=43 | | 1/2x+22=34 | | L=-3w-4 | | 8z+7=21 | | -3=x/7-1 | | 7r-9=4r | | 3/4(m-1)+4=6 |